2018
DOI: 10.1063/1.5017166
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated aqueous sodium chloride solution in clays at thermodynamic conditions of hydraulic fracturing: Insight from molecular dynamics simulations

Abstract: A relationship between the effect of uni-univalent electrolytes on the structure of water and on its volatility The Journal of Chemical Physics 148, 222807 (2018) To address a high salinity of flow-back water during hydraulic fracturing, we use molecular dynamics (MD) simulations and study the thermodynamics, structure, and diffusion of concentrated aqueous salt solution in clay nanopores. The concentrated solution results from the dissolution of a cubic NaCl nanocrystal, immersed in an aqueous NaCl solution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…51 force fields, respectively. The OPLS, SPC/E, and EPM2 force fields have been shown to satisfactorily reproduce the thermodynamic and vapor-liquid equilibrium properties, [52][53][54] additionally, the force fields are compatible with the CVFF. 47 The LJ crossinteractions were given by the Lorentz-Berthelot combining rules: 11…”
Section: Molecular Modelsmentioning
confidence: 85%
See 1 more Smart Citation
“…51 force fields, respectively. The OPLS, SPC/E, and EPM2 force fields have been shown to satisfactorily reproduce the thermodynamic and vapor-liquid equilibrium properties, [52][53][54] additionally, the force fields are compatible with the CVFF. 47 The LJ crossinteractions were given by the Lorentz-Berthelot combining rules: 11…”
Section: Molecular Modelsmentioning
confidence: 85%
“…For the hydrocarbons, water, and carbon dioxide, we employed the Optimized Potential for Liquid Simulations (OPLS), 48 the flexible Extended Simple Point Charge (SPC/E), 49,50 and the flexible Elementary Physical Model (EPM2) 51 force fields, respectively. The OPLS, SPC/E, and EPM2 force fields have been shown to satisfactorily reproduce the thermodynamic and vapor–liquid equilibrium properties, 52‐54 additionally, the force fields are compatible with the CVFF 47 . The LJ cross‐interactions were given by the Lorentz‐Berthelot combining rules: 11 εij=εiiεjj and σ ij = ( σ ii + σ jj )/2.…”
Section: Models and Methodologymentioning
confidence: 94%
“…For molecular simulations to reliably predict the properties of confined electrolytes, it is important that adequate force fields describe the interactions between water, electrolytes, and pore constituents, as well as all the cross-interactions between these components. 139,140 The reliability of the force fields used to describe the electrolytes depends on the model chosen to simulate water, and it is essential to tune the ion-ion interactions if one seeks to replicate the experimental salt solubility. 141,142 Svoboda and Lísal 140 recently employed the grand canonical Monte Carlo algorithm to predict the solubility of NaCl in montmorillonite pores.…”
Section: Aqueous Electrolytes In Confinementmentioning
confidence: 99%
“…The same amount of diffusivity for calcium and sulfate ions is due to strong ion association in a cluster structure. Svoboda and Lísal showed that ions’ self-diffusion coefficients in a solution change for different salinities. , In low-salinity cases, the small ions would experience higher hydration than the larger ions; therefore, they are more affected by surrounding water; hence, their mobility decreases. While in higher salinity solutions, ions’ self-diffusivities become similar because of the probability of ion association enhancement.…”
Section: Resultsmentioning
confidence: 99%